1987
DOI: 10.1080/00140138708966031
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of jet-lag and their alleviation by melatonin

Abstract: Seventeen healthy volunteers (10 women and 7 men, aged 29-68) were flown from London to San Francisco between 20 November 1985 and 25 January 1986 and remained there for 14 days prior to flight home. Subjects took melatonin (N= 8, 5 women, 3 men) or placebo in a double-blind design, at 18.00h local time for three days before the return flight and at bedtime (22.00-24.0011) in Great Britain for four days. For three days before departure and on days 1-7,14,15,21 and 22 after their retum subjects collected 6-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(93 citation statements)
references
References 13 publications
5
83
1
4
Order By: Relevance
“…Aaron Lerner may be the first person reported to have been successfully treated for ASPS with the neurohormone he discovered (0.3 mg of melatonin at wake time) (Lewy 2007). Other circadian phase disorders amenable to melatonin (and light) treatment include jet lag (Arendt et al 1987;Lewy et al 1995;Burgess et al 2003) and maladaptation to shift work (Sack et al 1992a). Treatment has not progressed rapidly in the area of shift work, due to many factors, such as rapidly changing schedules and the fact that DLMO time cannot even be grossly estimated from sleep times in these individuals.…”
Section: Circadian Disorders In Sighted Peoplementioning
confidence: 99%
“…Aaron Lerner may be the first person reported to have been successfully treated for ASPS with the neurohormone he discovered (0.3 mg of melatonin at wake time) (Lewy 2007). Other circadian phase disorders amenable to melatonin (and light) treatment include jet lag (Arendt et al 1987;Lewy et al 1995;Burgess et al 2003) and maladaptation to shift work (Sack et al 1992a). Treatment has not progressed rapidly in the area of shift work, due to many factors, such as rapidly changing schedules and the fact that DLMO time cannot even be grossly estimated from sleep times in these individuals.…”
Section: Circadian Disorders In Sighted Peoplementioning
confidence: 99%
“…For example, usefulness has been proposed for those working shifts, 18 or suffering jet lag, 19 chronic insomnia, 20 or delayed sleep phase syndrome. 21 Jan et al 15 found beneficial effects of melatonin in their 15 children (13 male) with severe chronic sleep disorders who had failed to respond to conventional psychological and social management.…”
Section: Melatoninmentioning
confidence: 99%
“…Results from studies examining phase shifts in eastward jet-travelers indicate that antidromic shifts are quite common. Early studies suggested that antidromic re-entrainment occurred in 1 of 7 people following an 8-h eastward flight (Arendt et al, 1987) and 4 of 8 people following a 9-h eastward flight (Klein et al, 1977).…”
mentioning
confidence: 99%